Case Study for Modernization of the Natal/RN Giga Metropole Network, in line with Recommendation ITU-T G.989 (NG-PON2) - Carvalho , Victor Fassanaro Cortez de; Silva, Gutembergue Soares da; Pinheiro, Fred Sizenando Rossiter (Seven Editora, 2023)
In recent years, the importance of improving the quality of internet services in public institutions has grown, especially those that work in the areas of Education, Health, and Safety, constituting an important tool for the social, economic, and cultural development of society. In this context, the National Teaching and Research Network–RNP, through the Community Teaching and Research Networks–REDECOMEP and its Points of Presence-PoPs, which operate on a high-speed network in the metropolitan region of Natal/RN, with infrastructure based on fiber optic network technology, interconnecting several public and private institutions, aiming to provide access to various services. The PoP-RN, with its Giga Metrópole and Giga Natal networks, based on G-PON (Gigabit Passive Optical Network) technology, serves public schools, universities, hospitals, UBS/UPAS, police stations, with a network extension of over 260 km. The work described in this article performs a structural and technological evaluation of this network and develops a case study to evaluate possible options to improve the provision of services to users, through modernization directed to more current standards, being chosen for analysis of the NG-PON2, governed by ITU-T G.989 recommendation which provides for a fiber capacity of 40 Gbit/s,  exploiting multiple wavelengths in dense wavelength division multiplexing channel spacing and tunable transceiver technology at user terminals. DOI:https://doi.org/10.56238/devopinterscie-242